Surgical Resection for a Second Primary Lung Cancer Originating Close to the Initial Surgical Margin for Lung Squamous Cell Carcinoma. (10th March 2015) - Sato, Seijiro; Koike, Terumoto; Hashimoto, Takehisa; Tsuchida, Masanori
Abstract : Few reports have described surgical resection for second primary lung cancers originating close to the initial surgical margin for lung cancer. A 64-year-old man had undergone left segmentectomy with lymph node dissection for small peripheral squamous cell lung cancer using video-assisted thoracic surgery, with pathology confirming a small tumor 12 mm in diameter identified about 3 cm from the surgical margin. Eighteen months after initial surgery, computed tomography revealed a 30 mm pulmonary nodule close to the initial surgical margin in the residual left upper lobe and the serum level of carcinoembryonic antigen was found to be increased. Local recurrence on the staple-line of the surgical margin was suspected, and completion left upper lobectomy was performed. Histological examination identified not only a squamous cell carcinoma component but also a small cell carcinoma component. The immunohistochemical staining pattern of the second tumor differed from that of the initial resected lung squamous cell carcinoma. The final pathological diagnosis was a second primary tumor with mixed small cell carcinoma and squamous cell carcinoma histology.